Flow injection on-line dialysis coupled to high performance liquid chromatography for the determination of some organic acids in wine - Orawan Kritsunankul (2018)
A combined system of flow injection on-line dialysis sample pretreatment and high performance liquid chromatographic separation/detection (FID-HPLC) was developed for simultaneous determination of six organic acids (tartaric, malic, lactic, acetic, citric and succinic acids). A sample or mixed standard solution (400 μL) was injected into a donor stream (water) of FID system and was pushed further through a dialysis cell, while an acceptor solution (water) was held in the opposite side of the dialysis membrane. The dialysate containing organic acids in the acceptor solution was then flowed to an injection loop of the HPLC valve, where it was further injected into the HPLC system and analysed under normal HPLC conditions, using a reversed-phase (C18) analytical column and UV detection (210 nm). The order of elution was tartaric, malic, lactic, acetic, citric and succinic acids with the analysis time of 8 min. The FID system could be operated in parallel with HPLC separation, providing sample throughput of 7.5 h-1. Dialysis efficiencies of six organic acids were in range of 4.6-9.5%. Calibration graphs for all the mentioned organic acids were linear over the range of 250-7500 mg L-1. Precisions for all the organic acids were within 5.4%. The proposed system was successfully applied for analysis of some Thai wines. By spiking wine samples with mixed acid standard solutions, the percentage recoveries in range of 84-104 were found. This system has advantages of fast and high degrees of automation for dialysis sample pretreatment, on-line sample separation and dilution, good clean-up for prolongation of life-time of the HPLC column and low consumption of chemicals and materials. Crown Copyright © 2009.